DECONSTRUCTING THE HISTORICAL NARRATIVE: A CRITICAL REVIEW OF THE ABSENCE OF A CONSTRUCTIVE ROLE OF THE SHIA FACTION IN THE PAST, PRESENT, AND FUTURE OF ISLAMIC CIVILIZATION - Rizaldy Alpiansyah; Isrun Abdurahman; Irfan Alkhotiri; Miftah Wangsadanureja; Dzulfikri (Mutamayyiz: Journal of Islamic Studies, 2026)
The discourse on the history of Islamic civilization is often dominated by narratives that romanticize inter-group harmony without giving adequate attention to a critical analysis of the disintegrative factions within it. This scientific article aims to examine, dissect, and deconstruct the claims regarding the Shia faction's contributions to achieving the glory of Islam. This study investigates the historical role, contemporary sociopolitical reality, and future projections of the Shia faction using a comparative-analytical (muqāran) historical approach based on orthodox classical literature and modern political studies. The results conclusively show that the absence of a positive Shia role is not an a priori assumption, but a well-documented historical fact. In the past, the existence of Shia political entities such as the Fatimid (Ubaydid) Dynasty in Egypt and the Safavid Dynasty in Persia consistently acted as subversive forces that destroyed the cohesion of the Ummah, hindered the expansion of Islam into Europe by allying with Christian empires, and facilitated the collapse of the Abbasid Caliphate in Baghdad in 1258 AD. At present, the theological anomalies inherent in Shia dogma—such as the exclusive Imamate cult, the doctrine of infallibility, and the rejection of the legitimacy of the early generations of the Prophet's Companions—have triggered severe creedal clashes. The transformation of this ideology into a political movement post-1979 Iranian Revolution has proven to spawn sectarian proxy wars that destroy the infrastructure of civilization in the Middle East and threaten social harmony in regions like Indonesia. Projecting into the future, this research concludes that the historical shackles and sectarian sentiments institutionalized in Shia theology will always be a stumbling block to the reconciliation of the Ummah. As long as the epistemology of hatred towards mainstream history is maintained, the Shia faction will remain an inhibiting variable that distances the Ummah from the ideals of unity and the revival of global Islamic civilization.